Maxwell distributions in a model of rough spheres - Gordevskii, V. D.; Gukalov, A. A.; Гордевский, В. Д.; Гукалов, А. А.; Гордевский, В. Д.; Гукалов, А. А. (Institute of Mathematics, NAS of Ukraine, 2011)
The Boltzmann equation is considered for the model of rough spherical molecules which possess both translati-onal and rotational energies. The general form of local Maxwell distributions for this model is obtained. The main possible types of corresponding flows of a gas are selected and analysed.